Synthesis, crystal structure, NMR characterization, Thermal analysis and Spectroscopic Characteristics of [2,3-(CH3)2C6H3NH3]6P6O18.2H2O - FEZAI, RAMZI; KHEDHIRI, LAMIA; RZAIGUI, MOHAMED (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Single crystals of [2,3-(CH3)2C6H3NH3]6P6O18.2H2O were synthesized in aqueous solution. This compound crystalizes in the P <!–?mso-application progid="Word.Document"?–> 141"> Â Triclinic unit cell with the parameters a = 9.97 Ã…, b = 16.06 Ã…, c =18.62 Ã…, Î± = 93.03Â°, Â b Â = 89.75 Â°, g = 93.85Â°, and Z = 2. Its crystal structure, determined by X-ray diffraction, consists of inorganic layers parallel to the ac plane. The organic molecules are disposed parallel to the plane bc on either side of each inorganic layer on which are anchored by hydrogen bonds via their ammonium groups (N-Hâ€¦O). Configuration of the asymmetric unit is characterized by FT-IR spectroscopy and solid state NMR study of 31P.